A comparative empirical investigation on the thermal performance of gravity-assisted double-bent, double-ended cooling, and single-bent, single-ended cooling heat pipes. (March 2020) - Habibnezhad Ledari, Behnam; Sabzpooshani, Majid
Abstract: Using of heat pipes is one of the best practical solutions that are considered for cooling processors and heat sources. A comparative study on the thermal performance of gravity-assisted double-bent, double ended cooling (DBDC) and single-bent, single-ended cooling (SBSC) heat pipes having sintered copper felt wick was proposed and evaluated experimentally. The DBDC and SBSC heat pipes are bendable post fabrication. Cooling blocks were elevated upper than the evaporator section of the heat pipes. The effects of heat input, bending angle, and using double condenser on the thermal performance were evaluated. The results showed that the minimum evaporator surface temperature for the DBDC and SBSC heat pipes occurred in the 60° and 45° bending angles respectively. Also the evaporator surface temperature of the DBDC heat pipes was less than SBSC heat pipes for bending angles lower than 60° while for bending angles more than 60° it was vice versa. The results indicated that the bending angle had a significant effect on the heat pipe's thermal performance. The minimum thermal resistance and maximum Nusselt number witnessed were 0.23857 °C/W and 7.51 × 10 5 respectively for DBDC heat pipe at the 60° bending angle, for the 70 W and 80 W heat inputs.